Hepatic clearance of Candida albicans in rats. - Sawyer, R T (1976)
The initial clearance of Candida albicans from the blood stream of rats and from perfusion medium by perfused rat livers was characterized. Normal rats cleared over 90% of large doses of intravenously injected yeast cells in 5 min. All were recovered as viable cells among various reticulendothelial organs after 30 min. The perfused rat liver trapped an average of 85% of the yeast cells in a single pass. No significant killing occurred, even in the presence of 10% whole rat blood. Scanning electron microscopy of cryofractured livers revealed that the cells were trapped in liver sinusoids but outside phagocytic cells.